2011
DOI: 10.1590/s1517-83822011000200036
|View full text |Cite
|
Sign up to set email alerts
|

The neem [Azadirachta indica a: juss (meliaceae)] oil reduction in the in vitro production of zearalenone by Fusarium graminearum

Abstract: Zearalenone, a mycotoxin produced by fungi of the genus Fusarium, including F. graminearum, triggers reproduction disorders in certain animals and hyperestrogen syndromes in humans. Current research investigates three concentrations of neem oil extract (0.1, 0.25 and 0.5%) in reducing the production of zearalenone. Neem oil extract decreased zearalenone amount in the three concentrations but highest inhibition (59.05%) occurred at 0.1%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Neem oil extract inhibits zearalenone production at 0.1-0.5% concentrations, but the highest inhibition (59.05%) of mycotoxin synthesis occurred at 0.1%. 49 The aqueous preparation of Neem leaves is found to be effective in activating immune responses against tumor antigens. Studies in experimental stages have shown that the extract, in combination with a breast tumor-associated antigen, was effective in initiating a strong IgG response as compared to the response generated by the breast cancerassociated antigen alone.…”
Section: Medicinal Usesmentioning
confidence: 99%
“…Neem oil extract inhibits zearalenone production at 0.1-0.5% concentrations, but the highest inhibition (59.05%) of mycotoxin synthesis occurred at 0.1%. 49 The aqueous preparation of Neem leaves is found to be effective in activating immune responses against tumor antigens. Studies in experimental stages have shown that the extract, in combination with a breast tumor-associated antigen, was effective in initiating a strong IgG response as compared to the response generated by the breast cancerassociated antigen alone.…”
Section: Medicinal Usesmentioning
confidence: 99%
“…Neem oil extract decreases zearalenone production at 0.1-0.5% concentrations, but the highest inhibition (59.05%) of mycotoxin synthesis occurred at 0.1% (Geraldo et al, 2011). Several species of Fusarium produce mycotoxins such as trichothecenes and zearalenone in cereal crops that are used as animal and poultry feed and can affect human and animal health if they enter the food chain.…”
Section: Efficacymentioning
confidence: 99%
“…Azadirachta indica also known as Margosa, neem or Indian lilac is a tree belonging to family Maliaceae. Leaf extract of margosa has been demonstrated to have antifungal action against a variety of fungi, and under the right circumstances, it is said to detoxify mycotoxins produced by FFSC complex (Mishra et al 1994;Mossini et al 2009;Geraldo et al 2011). Quercetin, a avonoid that differs from nimbosterol (β-sitosterol), and several limonoids, including Nimbin, are abundant in margosa leaves (Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%